MENUMBUHKAN SIKAP SOLIDARITAS PESERTA DIDIK DALAM MATA PELAJARAN SOSIOLOGI - Nurhayati; Daroe Iswatiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sociology education not only serves as a medium for delivering material, but also plays a role in shaping students' social attitudes, including solidarity. However, the reality in schools shows that student solidarity is still low, marked by the emergence of exclusive groups, a lack of cooperation, and a tendency toward individualism in learning. This study aims to describe the process of fostering solidarity among students through sociology learning, identify supporting and inhibiting factors, and formulate effective learning strategies so that solidarity values can develop in the learning environment. This study uses a qualitative approach with a descriptive method. Data were obtained through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that sociology learning is able to foster solidarity among students through group-based learning strategies (cooperative learning), class reflection, attitude assessment, and habituation through real social activities. Supporting factors in this process include the role of teachers as role models, a school culture that supports cooperation, and the application of collaborative learning models. Meanwhile, the obstacles found are individualistic character, low self-confidence, and uneven academic abilities within the group. Overall, sociology learning has been proven to be effective as a means of forming solidarity attitudes when implemented consistently, structurally, and oriented towards meaningful learning experiences.